IgG fractions from patients with antiphospholipid syndrome and systemic lupus erythematosus bind to platelets, but do not affect collagen-induced platelet activation. (17th November 2022) - Ho, YC.; Brake, SJ.; Ahuja, KDK.; Acott, N.; Tiao, J.; Baker, R.; Adams, MJ.
ABSTRACT: Anti-beta-2 glycoprotein 1 (anti-β2GP1) is an antiphospholipid antibody found in patients with antiphospholipid syndrome (APS) and systemic lupus erythematosus (SLE). Its presence commonly is associated with thrombosis; however, the mechanisms of interaction of anti-β2GP1 antibodies and platelets remain unclear. We investigated the effects of APS and SLE patient-derived IgG fractions on collagen-mediated platelet aggregation and examined the binding of patient-derived IgG to platelets before and after activation by collagen. IgG fractions, 150, 200, 300 or 350 µg/ml, isolated from 11 patients with APS and SLE were incubated with two sets of platelet-rich plasma (PRP) in the incubation wells of an aggregometer. The first set was activated by collagen and the other set was incubated for an additional 10 min. All platelets were collected by centrifugation and fixed in cell blocks. We assessed binding of IgG to platelets using immunocytochemistry (ICC). Patient-derived IgG fractions did not affect collagen-induced platelet aggregation. ICC staining using anti-human IgG antibodies demonstrated that patient-derived IgG fractions had greater affinity for non-activated platelets than those activated by 0.75 µg/ml collagen. Patient-derived IgG fractions bound to the surface of platelets and potentially could be internalized by platelets. IgG fractions from APS and SLE patients may sensitize non-activated platelets, which could increase platelet reactivity and thrombotic risk in patients. We did not detect secondary effects of patient-derived IgG fractions.